Fun and E-learning (A Hybrid Teaching Factory Model) - Dewi Nurmalasari; Astri Yulia; Izyani Mat Rusni (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Educators must possess the capacity to create engaging instructional sessions that are tailored to specific time periods and generational attributes. This study explores the concept of an engaging educational setting within the context of the generation Z period. Furthermore, technological advancements have offered individuals supplementary prospects to cultivate and nurture social connections in what is commonly referred to as e-learning. Classroom management encompasses the coordination of classroom activities to enhance learning, along with the teacher's proficiency in creating an optimal learning environment through the use of technology, in line with the demands of the digital era, to address any challenges that arise during the learning process. The primary objectives of utilizing (digital) technology in classroom management are to enhance the learning quality and maximize the overall learning experience (e-learning). Attaining educational objectives is essential for guaranteeing the excellence of the learning process. Classroom management abilities encompass educators' capacity to effectively establish and sustain an ideal educational setting by adeptly employing technology in accordance with contemporary trends and the distinctive learning attributes of Generation Z students. Efficiently managing the teaching and learning process requires a systematic approach that encompasses tasks such as planning, organizing, controlling, and supervision. These actions are conducted concurrently, thoroughly, and in an integrated manner. A learning approach using technology carried out in a hybrid according to the teaching factory concept is a good solution for achieving learning objectives.